Editorial: Fight against food waste: tackling pre-harvest diseases - Siddiqui, Yasmeen; Kumar, Ajay; Srivastava, Ashish (Frontiers in Microbiology, 2023)
In a world where millions suffer from hunger and malnutri4on, the shocking reality is that nearly one-third of the total food produced is wasted. Although food wastage occurs at the various stages of the supply chain, one o>en overlooked area where significant losses occur is pre-harvest diseases. Preharvest diseases have no boundaries and affect the crops in both developed and developing na4ons with consequences reverbera4ng throughout the food supply chain. Farmers face tremendous challenges in trying to control these diseases, o>en resor4ng to excessive pes4cide use, which not only harms the environment but also contributes to the development of pes4cide-resistant pathogens Addressing preharvest diseases is a mul4faceted endeavour that requires a holis4c approach. Recent research has paved the way for innova4ve approaches to protec4ng crops without harming the environment or human health. In this editorial, we highlight six groundbreaking studies that shed light on eco-safe alterna4ves to conven4onal pes4cides and offer promising strategies for managing diseases affec4ng crops.